Perfil clínico-epidemiológico e sociodemográfico de pacientes HIV/AIDS co-infectados com toxoplasma Gondii em região de fronteira - Moro, Janielle Chrislaine (2020)
Introduction: HIV/AIDS infection is currently a problem of major concern for the world public health sphere, due to the continuous growth of the infection in the population. Dysfunctions due to HIV infection make the body vulnerable to opportunistic diseases, and among those affecting the central nervous system, toxoplasmosis is the most frequent and is the leading cause of focal neurological damage in HIV-infected patients. Objective: To investigate the clinical-epidemiological and sociodemographic profile and risk factors of patients diagnosed with HIV/AIDS co-infected with T. gondii in the municipality of Foz do Iguaçu. Material and methods: This is a comparative study and a quantitative approach. We evaluated 332 HIV-positive patients followed at the Specialized Assistance Service (SAE) in Foz do Iguaçu/PR. Information was obtained through research in medical records and by applying a structured and adapted questionnaire containing 27 objective questions, composed of the following sections: socioeconomic, demographic and psycho-social information (gender, age, color/race, education, nationality, marital status and family income) and issues associated with risk factors related to the transmission of toxoplasmosis (knowledge, orientation and behavioral habits). Data were tabulated using Excel® software. The association between the parasitized state (dependent variable) and the independent variables was evaluated. Chi-square (X2) and Pearson test. All variables that obtained p≤0.20 in the chi-square analysis were included in the Odds Ratios (OR) multivariate analysis, 95% confidence interval, α <0.05). Analyzes were performed using BioEstat version 5.3® software. Results: Of the 332 patients with HIV/AIDS analyzed, 111 had toxoplasmosis serology in their medical records, indicating a high rate of T. gondii infection. There was a prevalence among individuals aged ≥ 18 and ≤ 60 years, patients who studied up to the 4th grade of elementary school and or higher education (incomplete/complete) (p <0.05). In addition, a higher prevalence was observed among those who consume raw salad outside the home, who handle soil / soil without wearing gloves, consume untreated water and patients who report that neighborhood cats enter their homes ( p <0.05). The following risk factors remained in the final model after multivariate logistic analysis: patients with 3rd degree (incomplete/complete) and patients who consumed well water were more likely to acquire T. gondii infection at 0.2 and 3, 0 times more, respectively. Neurotoxoplasmosis (3.31%) and ocular toxoplasmosis (3.61%) were detected. In addition, 54.1% (60/111) of the patients had CD4 T <200, of which 56.8% (46/60) tested positive for anti-T IgG. gondii. Conclusion: This work allowed a characterization of the profile of patients infected with HIV/AIDS and co-infected with toxoplasmosis in a triple frontier municipality, being a pioneer study in the region. The results obtained contribute considerably to public health at the municipal and state levels, providing data to encourage the implementation of effective measures to control morbidity and mortality associated with this disease in the population evaluated.